Matha (monastery/religious building) in the Mahanaleshwar Temple Complex - Temples of India Project Team (Jio Institute, 2024)
Matha (monastery/religious building) in the Mahanaleshwar temple complex. The two-storeyed structure was built by a sage named Bhava Brahma, of the Mattamyura tradition, during the reign of Cahamana King Prithviraja II in the 12th century CE. The Matha is one of the finest examples of residential buildings found in Central India.